Development Of Local Content Agricultural Learning Tools In Elementary Schools In Enrekang Regency - Derman; Patta Bundu; Bahkrani A. Rauf (International Journal of Education Management and Religion, 2026)
This study aims to develop relevant and contextual local agriculture learning tools for elementary school students in Enrekang Regency. Local potential-based education is an effective strategy for instilling local wisdom values from an early age. However, initial observations show that most elementary schools in Enrekang Regency do not yet have well-structured learning tools that are in line with the socio-cultural characteristics of the region. The development model used in this study is the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model, which is a systematic process for producing valid, practical, and effective learning tools. The results of the study show that the learning tools developed have a very high level of validity with an average score of 87.74%. The practicality of the tools reached an average of 86.91%, based on observations of implementation and positive responses from teachers and students. In terms of effectiveness, there was a significant increase in student learning outcomes from an average of 71.3 on the pretest to 84.1 on the posttest, with a gain score of 0.72, which is classified as high.